PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (UD. MEKAR JAYA SENTRA INDUSTRI TEMPE SANAN KOTA MALANG) - Irfan Candra Wardana; Hadi Sunaryo; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRAKCTThis study aims, to find out and describe the influence of the work environment, job satisfaction, and work motivation on employee performance at UD. Mekar Jaya Malang. To find out and describe the work environment, job satisfaction, and work motivation on employee performance at UD. Mekar Jaya Malang. To find out and describe the influence of the work environment on employee performance at UD. Mekar Jaya Malang. To find out and describe job satisfaction on employee performance at UD. Mekar Jaya Malang. To find out and describe work motivation on employee performance at UD. Mekar Jaya Malang. Keywords: Work environment, Job satisfaction, Work motivation, Employee performance